Protective effects of Chinese Fenggang zinc selenium tea on metabolic syndrome in high-sucrose-high-fat diet-induced obese rats - Jie Yu (Nature Portfolio, 2018)
Abstract The protective effect of zinc selenium tea against metabolic syndrome (MetS) was tested by using a high-sucrose-high-fat diet (HSHFD)-induced MetS model. Fifty Sprague–Dawley rats were randomly divided into five groups: normal diet (C-group), HSHFD (CH-group), HSHFD + green tea (0.24 g/kg/day) (TH-group), HSHFD + low-dose zinc selenium organic tea (0.24 g/kg/day) (ZTHL-group), and HSHFD + high-dose zinc selenium organic tea (1.20 g/kg/day) (ZTHH-group). After 8 weeks, compared to both the C-group and CH-group, the hepatosomatic index (HI) was significantly reduced in the ZTHL-group (p < 0.05). Fasting blood glucose (FBG) levels were highest in the TH-group, followed by the CH-group, then the ZTHL-group, then the ZTHH-group, and finally the C-group. Compared with the CH-group, the serum total cholesterol (TC) and low density lipid-cholesterol (LDL-C) concentrations were significantly lower in the ZTHH-group (p < 0.05). Significant decreases in serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bile acids (TBA), alkaline phosphatase (ALP), and direct bilirubin (DBIL) levels were observed in ZTHL-group versus the CH-group (p < 0.05). Serum alpha-L-fucosidase (AFU) levels in the ZTHH-group were lower than in the CH-group (P < 0.01). Histopathological examination of the liver and fat biopsies illustrates that the liver cells showed a decrease in the extent of necrosis and dropsy in the ZTHL-group and ZTHH-group versus the CH-group. Zinc selenium tea showed a protection effect against hepatic damage.